2022
DOI: 10.1177/20578911221076234
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pilgrim tourism on the bilateral diplomacy of India and Nepal and the mediation effect of people-to-people contact

Abstract: The present article aims to analyse the impact of pilgrim tourism on bilateral relations and to identify the mediating effect of people-to-people contact. It further proposes to test the framework empirically in the neighbouring context of India and Nepal. To achieve the objective, random sampling is used, and 380 usable questionnaires are taken for testing the theoretical framework. Structural Equation Modelling (SEM) is used to assess the framework's fit and analyse the impact of pilgrim tourism on bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Tourism promotes participatory peacemaking to foster mutual understanding and cooperation among cultures (Causevic, 2010;Wani et al, 2022). There are many reasons why regional assimilation can be achieved through the territorial cooperation process, which is considered a fundamental political procedure to reduce the barriers posed by all kinds of borders and to promote territorial development (Knippschild, 2011;Dada et al, 2022). Depending on the region's characteristics, the mix of available resources, the strategies and activities devoted to promoting tourism, and cross-border collaboration, tourism can catalyze economic development in cross-border regions (European Commission, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Tourism promotes participatory peacemaking to foster mutual understanding and cooperation among cultures (Causevic, 2010;Wani et al, 2022). There are many reasons why regional assimilation can be achieved through the territorial cooperation process, which is considered a fundamental political procedure to reduce the barriers posed by all kinds of borders and to promote territorial development (Knippschild, 2011;Dada et al, 2022). Depending on the region's characteristics, the mix of available resources, the strategies and activities devoted to promoting tourism, and cross-border collaboration, tourism can catalyze economic development in cross-border regions (European Commission, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interacting with other people and exchanging ideas is at the heart of tourism's mission to foster understanding and decrease barriers between different cultures (Sharma et al, 2018). Several empirical studies have demonstrated the importance of tourism in promoting peace (e.g., Kim and Prideaux, 2006;Cho, 2007;Dada et al, 2022). Due to reduced transit costs, cross-border tourism helps to construct infrastructure, improving trade flows (Setnikar Cankar et al, 2014).…”
Section: Cross-border Tourismmentioning
confidence: 99%
See 3 more Smart Citations